Poststroke epilepsy: current perspectives on diagnosis and treatment - Sarecka-Hujar B (Dove Medical Press, 2018)
Beata Sarecka-Hujar,1 Ilona Kopyta2 1Department of Pharmaceutical Technology, School of Pharmacy with the Division of Laboratory Medicine in Sosnowiec, Medical University of Silesia in Katowice, Sosnowiec, Poland; 2Department of Paediatric Neurology, School of Medicine in Katowice, Medical University of Silesia in Katowice, Katowice, Poland Abstract: Seizures and epilepsy are quite a common outcome of arterial ischemic stroke (AIS) both in pediatric and adult patients, with distinctly higher occurrence in children. These poststroke consequences affect patients’ lives, often causing disability. Poststroke seizure (PSS) may also increase mortality in patients with AIS. Early PSS (EPSS) occurring up to 7 days after AIS, late PSS (LPSS) occurring up to 2 years after the onset of AIS, as well as poststroke epilepsy (PSE) can be distinguished. However, the exact definition and cutoff point for PSE should be determined. A wide range of risk factors for seizures and epilepsy after AIS are still being detected and analyzed. More accurate knowledge on risk factors for PSS and PSE as well as possible prediction of epileptic seizures after the onset of AIS may have an impact on improving the prevention and treatment of PSE. The aim of the present review was to discuss current perspectives on diagnosis and treatment of PSS and PSE, both in adult and paediatric patients. Keywords: arterial ischemic stroke, early seizures, late seizures, antiepileptic treatment